Mangroves and their medicinal benefit: a mini review - Leticia Andina Genilar; Evi Kurniawaty; Ruzaidi Azli Mohd Mokhtar; Kholis A. Audah (Vasile Goldis Western University of Arad, 2021)
Mangrove plants have been utilized by humankind for so long. It is widely suggested that there are still many benefits to these mangroves that are not yet discovered. This article examines the current researches in the usage of mangroves as medicine. Many of these researches revolve around the potential use of mangrove as anticancer, antitumor, anti-inflammatory, antifungal, antibacterial, antiviral, and antidiabetic. Studies have shown that mangroves indeed have numerous benefits and untapped potential in the medical field. This article will also review the current state of conservation and preservation of mangrove plants in the world.